Motivation and Work Environment on Employee Performance - Harlindah Harniati Arfan (Cendekiawan Indonesia Timur, 2021)
This research aims to identify and evaluate the effects of motivation and work environment on employee performance. This study was carried out in South Sulawesi Province, and it used a literary design with a qualitative method. Purposive sampling, i.e., direct appointment by the researcher, was employed in the sampling method. Techniques for gathering data include observation, interviews, surveys, and recordkeeping. Data analysis involves reducing, presenting, and deriving conclusions from data. The findings revealed that motivation and work environment might have a direct impact on performance. The typical employee is highly motivated, with intense excitement in carrying out their tasks and obligations, maximal efforts, and precise work instructions. Meanwhile, the work environment influences employee performance by fostering positive relationships with coworkers, providing a pleasant working environment, and making available work facilities.